(untitled) (Islamic Sciences Journal, 2023)
Legal systems, authorities and organizations of all kinds, and their tendencies, have tended to strive towards the issuance of preventive and legal and criminal provisions related to the serious epidemic that has swept the world and called the Coronavirus (COVID-19 TEST) .The emerging, and the serious and contagious disease in an unprecedented speed in an unprecedented manner over the successive periods of Times through the ages and history. Likewise, the developed countries in the world did not stand in front of him, starting with China, which started the disease first, then Iran, and other developed countries (France, Italy, Britain, Spain, Germany, and the United States of America) and lately the developed and Arab countries. Accordingly, a legal and criminal responsibility of individuals and authorities must be explained. In what case is the legal and criminal responsibility of individuals, and when it becomes shared.